Shema as Paradigm (Dt. 6:4–9) The Bible, Education, and the Quest for Development in Contemporary Ghana - Mensah, Michael Kodzo 1975- (2023)
It has been sixty-five years since Ghana, the first black African country south of the Sahara, gained independence from colonial rule. Since then, Ghana can boast of an educational system, which has churned out hundreds of thousands of graduates over the years. Despite these achievements, the country remains poor, raising questions about whether its educational system is fit for purpose. Meanwhile, the moral fibre of society seems to be crumbling with corruption, threatening to thwart any gains made since independence. Given the fact that over 70% of Ghanaians profess Christianity, and the Church’s active involvement in education, a resolution of the problem cannot exclude a religious and hence a biblical dimension. This paper, using the distinct interest approach of African Biblical Hermeneutics, argues that Deuteronomy 6:4-9 contains a paradigm for transformative education applicable to the challenges Ghana faces. It demonstrates that the instructions to love YHWH with the whole heart, the whole soul, and the whole might, relate to an education that creatively engages the intellectual faculty, one that is holistic and oriented towards the common good. These are necessary ingredients for the transformation and development of society and equally underscore the role of biblical discourse in building a future for Africa.
Keywords: African Biblical Hermeneutics; Deuteronomy 6:4–9; Development; Education; Ghana; Shema